2022
DOI: 10.1093/infdis/jiac068
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Effect of Preexisting Immunity on Influenza Vaccine Responses Transcends the Impact of Vaccine Formulation Type and Vaccination History

Abstract: The most effective measure to induce protection from influenza is vaccination. Thus, yearly vaccination is recommended, which, together with infections, establishes diverse repertoires of B cells, antibodies and T cells. Here, we examined the impact of this accumulated immunity on human responses of adults to split, subunit and recombinant protein-based influenza vaccines. ELISA assays, used to quantify serum antibodies and peptide-stimulated CD4 T cell cytokine ELISpots, revealed that pre-existing levels of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Annually repeated influenza vaccination attenuates the antibody response to inactivated influenza vaccines [16,[27][28][29][30][31][32][33]. Consistently, we found that individuals previously vaccinated exhibited a reduced fold-increase in HI titers and lower SCR postvaccination, compared with those without prior vaccination in the past 3 years.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Annually repeated influenza vaccination attenuates the antibody response to inactivated influenza vaccines [16,[27][28][29][30][31][32][33]. Consistently, we found that individuals previously vaccinated exhibited a reduced fold-increase in HI titers and lower SCR postvaccination, compared with those without prior vaccination in the past 3 years.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, the levels of influenza-specific CD4 T cell activation and pre-existing antibodies are correlated with a robust early vaccine-induced antibody response and strongly correlated with vaccination history [14]. Although vaccine-induced influenzaspecific CD4 T cell responses have positive correlations with serological responses, repeated annual influenza vaccination may impair CD4 T cells, causing defects in eliciting antibody responses [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of IgG‐titer increases in HRs was inversely correlated with pre‐existing titers, reflecting the “antibody ceiling effect” previously reported for HI and IgG responses during infection 24,25 and vaccination 13,16,26,27 . High titers of pre‐existing antibodies could lead to more rapid antigen clearance, 28,29 leading to limited activation of pre‐existing CD4+ T cells and memory B cells 24 . However, a ceiling effect for IgG responses was not detrimental since HRs, in which it was more evident, were still capable of mounting robust HI‐antibody responses.…”
Section: Discussionmentioning
confidence: 57%
“…Our findings suggest that host inflammatory status and pre‐existing influenza immunity can impact influenza vaccine responses through different mechanisms. The older poor vaccine responders may be immunologically restricted in their ability to generate vaccine‐specific HI‐responses, but pre‐existing influenza‐specific B cells can still be activated to produce IgG antibodies, 14,24 although this boosting appears to have a threshold. The magnitude of IgG‐titer increases in HRs was inversely correlated with pre‐existing titers, reflecting the “antibody ceiling effect” previously reported for HI and IgG responses during infection 24,25 and vaccination 13,16,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…The IFN-g ELISpot and intracellular cytokine staining (ICS) assays are frequently used to examine cellular immune responses elicited by influenza infection or vaccination (16)(17)(18)(19)(20)(21). A better insight into the magnitude, quality and durability of cellmediated immune responses can improve our understanding of the immunological mechanisms underlying viral clearance or vaccine effectiveness and may contribute to the identification of new correlates of protection.…”
Section: Discussionmentioning
confidence: 99%